An alternate way of collecting, storing, and dissecting Neurospora asci. - R. L. Metzenberg (Fungal Genetics Reports, 1988)
Tetrad analysis may be accomplished either with ordered asci squeezed from perithecia, or with asci shot as an unordered group at a target slab of agar (Perkins 1966, Neurospora Newsl. 9:11).